FLUTUAÃ‡ÃƒO POPULACIONAL DE ALGUNS CALLIPHORIDAE (DIPTERA) EM POMAR DE GOIÃ‚NIA, GOIÃS, BRASIL - Santos, Benedito Baptista dos; Ferreira, Maria Judy de Mello; Cunha, HÃ©lida Ferreira da (REVISTA DE AGRICULTURA, 2015)
FLUTUAÃ‡ÃƒO POPULACIONAL DE ALGUNS CALLIPHORIDAE (DIPTERA) EM POMAR DE GOIÃ‚NIA, GOIÃS, BRASIL